Spanish Validation of the Music in Dementia Assessment Scales. (30th March 2023) - Forn, Lourdes; Muñiz, Sergi; Alavedra, Cristina; Farràs-Permanyer, Laia; Signo, Sara; Bruna, Olga
Abstract: Music therapy has been described as a beneficial intervention for people with dementia. To provide a music therapy outcome measure, McDermott et al. (2015) developed the Music in Dementia Assessment Scales (MiDAS). The preliminary original validation indicated that MiDAS had acceptable to good psychometric properties. This study aimed to present the translation and cross-cultural adaptation of the MIDAS to the Spanish language and to show some validity sources using the Spanish version of the scale. MiDAS was adapted following the guidelines of Beaton et al. (2000), Muñiz et al. (2013) and Ridder et al. (2015), A psychometric validation study was conducted with a sample of 80 care home residents with moderate-severe dementia. Acceptable reliability values according to Cronbach's alpha were obtained, as was good interobserver reliability at one rating time point, based on Kendall's W test. The concurrent criterion validity values were positive, particularly in terms of the correlation coefficients of the criterion measure (specifically, the QoL-AD measures) and the item analysis, as shown by the correlation matrices. A one-factor confirmatory factor analysis (CFA) did not indicate a good fit for the obtained models, but acceptable and optimal values were observed for various parameters. The results indicate the usefulness of this tool, with sources of evidence of validity and reliability, although it is necessary to note the limitations of some of the results, as in the construct validity analysis. The MiDAS-ESP is a useful tool in clinical practice that can be used for measuring the effect of music therapy.